DEVELOPMENT OF GIS-TECHNOLOGY OF A SOFTWARE TO THE RELATION TO THE INTEGRAL ESTIMATION OF POLLUTION OF ATMOSPHERIC AIR IN CITIES OF UKRAINE - Білогуров, Віктор Петрович; Івахненко, Олександр Павлович (Eastern-European Journal of Enterprise Technologies, 2010)
The method of integral evaluation of air pollution in cities of Ukraine was considered. A GIS technology was created, which allows analysis of the ecological state of the atmosphere and determine problem areas.